Meta-analysis: Influence of host and viral factors in patients with chronic hepatitis C genotype 4 treated with pegylated interferon and ribavirin - Yee, Brittany E. (2014)
BACKGROUND: The burden of hepatitis C virus genotype 4 (HCV-4) is high in Africa and East Mediterranean countries. Previous reports estimate sustained virologic response (SVR) rates in HCV-4 to be ~20–70%. However, many of these studies are limited by different study designs and small sample sizes. AIM: Our aim was to evaluate treatment outcome and host/viral factors on SVR in HCV-4 patients treated with pegylated interferon and ribavirin (PEG IFN+RBV) in a systematic and quantitative fashion. METHODS: A comprehensive literature search in MEDLINE and EMBASE for ‘genotype 4’ was conducted in November 2013. Abstracts from AASLD, APASL, DDW, and EASL in 2012/2013 were reviewed. Inclusion criteria were original studies with ≥25 treatment-naïve HCV-4 patients treated with PEG IFN+RBV. Exclusion criteria were co-infection with HIV, HBV, or other genotypes. Effect sizes were calculated using random-effects models. Heterogeneity was determined by Cochrane Q-test (p-value <0.05) and I-squared statistic (>50%). RESULTS: We included 51 studies (11,102 HCV-4 patients) in the primary analysis. Pooled SVR was 53% (95% CI: 50–55%) (Q-statistic = 269.20, p<0.05; I(2) = 81.43). On sub-group analyses, SVR was significantly associated with lower viral load, OR 3.05 (CI 1.80–5.17, p<0.001); mild fibrosis, OR 3.17 (CI 2.19–4.59, p<0.001); and favorable IL28B polymorphisms, rs12979860 CC versus CT/TT, OR 4.70 (CI 2.87–7.69, p<0.001), and rs8099917 TT versus GT/GG, OR 5.21 (CI 2.31–11.73, p<0.001). CONCLUSIONS: HCV-4 patients treated with PEG IFN+RBV may expect SVR rate of ~50%. Lower viral load, mild fibrosis, and favorable IL28B (rs12979860 CC and rs8099917 TT) are positively associated with SVR.